Medical Therapy of Aggressive Pituitary Tumors - Petersenn, Stephan (Experimental and Clinical Endocrinology & Diabetes, 2021)
The rare aggressive pituitary adenoma presents a special challenge, due to the heterogenous presentation of the disease. The prognosis of aggressive pituitary adenomas has been improved due to recent studies demonstrating clinically-relevant efficacy of temozolomide, which is now considered first-line chemotherapy. However, there is limited data on second-line therapies in patients with treatment failure. This review presents a summary on the potential of medical therapies in aggressive pituitary tumors.
Keywords: carcinoma; chemotherapy; temozolomide; bevacizumab; tyrosine kinase inhibitor; everolimus; cyclin-dependent kinase inhibitor; checkpoint inhibitor